The Application of Al-Qur'an Surah Ar-Rahman Recitation Therapy on Hemodynamic Status in Stroke Patients at Dr. Soediran Mangun Sumarso Regional General Hospital, Wonogiri - Khotimah, Damayyanti Nur; Prajayanti, Eska Dwi; Sumardi (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Stroke is a disruption of blood flow to the brain that can cause hemodynamic instability, leading to complications and even death. Its prevalence is high in Indonesia, including at Dr. Soediran Mangun Sumarso Regional General Hospital, Wonogiri. Stroke management can be supported with non-pharmacological therapies, such as listening to the recitation (murottal) of the Qur’an. Surat Ar-Rahman is believed to have a relaxing effect and help stabilize bodily functions. Objective: To determine the application of Qur’anic Murottal Therapy (Surat Ar-Rahman) on hemodynamic status in stroke patients in Dr. Soediran Mangun Sumarso Regional General Hospital, Wonogiri. Method: This study used a descriptive case study with a pre-test and post-test design. The therapy was applied to two respondents for 15–20 minutes over three days. Results: The results showed decreased hemodynamic parameters after implementing Qur’anic Murottal Therapy (Surat Ar-Rahman). This therapy can be considered a non-pharmacological technique or an independent nursing intervention for inpatients in the stroke unit with unstable hemodynamic status. Conclusion: Qur’anic Murottal Therapy of Surat Ar-Rahman can serve as a non-pharmacological or independent intervention for improving hemodynamic status in stroke unit inpatients.